1985
DOI: 10.1523/jneurosci.05-11-02963.1985
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of barbiturate-stimulated chloride efflux from rat brain synaptoneurosomes

Abstract: Membrane chloride (Cl-) permeability was studied in a novel subcellular brain preparation, the synaptoneurosome. Using a radioactive tracer exchange technique, Cl- transport was determined by measuring 36Cl- efflux from rat cerebral cortical synaptoneurosomes. Barbiturates increased 36Cl- efflux in a dose-dependent manner with the following relative order of potency: 5-(1,3-dimethylbutyl)-5-ethyl barbituric acid ((-)-DMBB) greater than pentobarbital greater than secobarbital greater than (+)-DMBB greater than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
40
0
2

Year Published

1986
1986
1998
1998

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(45 citation statements)
references
References 33 publications
3
40
0
2
Order By: Relevance
“…Pharmacologically relevant concentrations of intravenous anesthetics (e.g., barbiturates, etomidate, alphaxalone, propofol) produce multiple actions at GABAA receptors (Ashton et al, 1981;Schwartz et al, 1985;Moody et al, 1988;Lin et al, 1992). Although previous studies have demonstrated that a /3 subunit is required for the GABA-positive actions of a range of structurally unrelated intravenous agents in recombinant receptors composed of a 1/32/3 y2 subunits (Harris et a!., 1995), this report identifies a specific amino acid necessary for action of etomidate at this receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacologically relevant concentrations of intravenous anesthetics (e.g., barbiturates, etomidate, alphaxalone, propofol) produce multiple actions at GABAA receptors (Ashton et al, 1981;Schwartz et al, 1985;Moody et al, 1988;Lin et al, 1992). Although previous studies have demonstrated that a /3 subunit is required for the GABA-positive actions of a range of structurally unrelated intravenous agents in recombinant receptors composed of a 1/32/3 y2 subunits (Harris et a!., 1995), this report identifies a specific amino acid necessary for action of etomidate at this receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Radioactivity was determined by liquid scintillation spectrometry. A full characterization of the effects of various barbiturates and GABA receptor agonists and antagonists on 36CP-efflux and uptake has been reported elsewhere (29)(30)(31)33 (34) and of Rohde and Harris (35). RESULTF Addition of ethanol to cerebral cortical synaptoneurosomes stimulated 36CJ-uptake in a dose-dependent fashion (Fig.…”
mentioning
confidence: 89%
“…Recently, we have reported the use of the "synaptoneurosome," a subcellular brain preparation, to measure GABA/ barbiturate receptor-mediated Cl-transport in vitro (29)(30)(31). Morphologic characterization of this preparation has revealed the presence ofboth pre-and postsynaptic membranes that form closed vesicles (32 (29,30) for measurement of 36C-efflux.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Biochemical studies suggest that barbiturates exert these effects at specific recognition sites located at or near GABAgated chloride channels. These so called "barbiturate receptors" (9) are allosterically linked to both GABAA and benzodiazepine receptors (9)(10)(11)(12)(13)(14)(15)(16), and this family of allosterically linked recognition sites, the "supramolecular complex" (17), is presumed to mediate the pharmacological actions of many agents that alter neuronal excitability at GABA-gated chloride channels.…”
Section: Introductionmentioning
confidence: 99%